EFFECT OF DIGITAL COMMUNITY TOWARDS DEMOCRACY PROCESS: DIGITAL PARTISIPATION ANALYSIS IN INDONESIA - Alih Aji Nugroho (Lembaga Administrasi Negara, 2020)
The world is entering a new phase of the digital era, including Indonesia. The unification of the real world and cyberspace is a sign, where the conditions of both can influence each other (Hyung Jun, 2018). The patterns of behavior and public relations in the virtual universe gave rise to new social interactions called the Digital Society. One part of Global Megatrends has also influenced public policy in Indonesia in recent years. Critical mass previously carried out conventionally is now a virtual movement. War of hashtags, petitions, and digital community comments are new tools and strategies for influencing policy. This paper attempts to analyze the extent of digital society's influence on public policy in Indonesia. As well as what public policy models are needed. Methodology used in this analysis is qualitative descriptive. Data collection through literature studies by critical mass digital recognition in Indonesia and trying to find a relationship between political participation through social media and democracy. By processing the pro and contra views regarding the selection of social media as a level of participation, this paper finds that there are overlapping interests that have the potential to distort the articulation of freedom of opinion and participation. - which is characteristic of a democratic state. The result is the rapid development of digital society which greatly influences the public policy process. Digital society imagines being able to participate formally in influencing policy in Indonesia. The democracy that developed in the digital society is cyberdemocracy. Public space in the digital world must be guaranteed security and its impact on the policies that will be determined. The recommendation given to the government is that a cyber data analyst is needed to oversee the issues that are developing in the digital world. Regulations related to the security of digital public spaces must be maximized. The government maximizes cooperation with related stakeholders.Keywords: Digital Society; Democracy; Public policy; Political Participation